1994
DOI: 10.1002/ar.1092390106
|View full text |Cite
|
Sign up to set email alerts
|

A morphological study of the lymphocyte traffic in Peyer's patches after an in vivo antigenic stimulation

Abstract: Our finding is that the passage of lymphocytes to the lumen is an antigen-dependent event and we also provide direct evidence that M cells are one of the migration routes. Our observations also indicate that lymphoid cells in the intestinal lumen may play an immunologic role in mucosal immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 17 publications
(19 reference statements)
3
17
0
Order By: Relevance
“…This structural heterogeneity, however, cannot be explained simply by the difference in the stage of M cell maturation (Spit et al 1989). In turn, there is a possibility that the excessive influx of immunocompetent cells into FAE might subsequently induce some subcellular changes in M cells (Regoli et al 1994). This is also suggested by the present observation that M cells in SPF-CV rats showed a relative increase in keratin filaments and electrondense spherical bodies, and extensive cytoplasmic interfoliation.…”
Section: supporting
confidence: 66%
See 1 more Smart Citation
“…This structural heterogeneity, however, cannot be explained simply by the difference in the stage of M cell maturation (Spit et al 1989). In turn, there is a possibility that the excessive influx of immunocompetent cells into FAE might subsequently induce some subcellular changes in M cells (Regoli et al 1994). This is also suggested by the present observation that M cells in SPF-CV rats showed a relative increase in keratin filaments and electrondense spherical bodies, and extensive cytoplasmic interfoliation.…”
Section: supporting
confidence: 66%
“…In fact, the infiltration of immunocompetent cells into the FAE containing M cells was increased when the duration of maintenance under conventional conditions was protracted. Lymphocyte migration into M cells therefore seems to be an antigendependent event (Regoli et al 1994), and the immune cells in the FAE appear to be able to induce an increase in the number of M cells (Fo$ rster et al 1996) and alterations in the FAE (Borghesi et al 1996). This structural heterogeneity, however, cannot be explained simply by the difference in the stage of M cell maturation (Spit et al 1989).…”
Section: mentioning
confidence: 99%
“…In other studies, however, discontinuities appeared to contain different types of cells: some resembled migratory lymphocytes (Nair and Rossinsky 1984), while others were rounded cells with either a villous or a smooth surface (Maeda et al 1978). These differences in cell appearance may reflect deformation of the M cell cytoplasm produced by lymphocytes migrating to the gastrointestinal lumen (Regoli et al 1994). Such migration, however, appears to be largely antigen-dependent (Heatley and Bienenstock 1982;Regoli et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although M cells have been studied for Makala/Nishikawa/Suzuki/Nagasawa ]. An immunological role for M-cell-associated lymphocytes is suggested by the observation that their numbers increase after application of a bacterial challenge [18,107]. The authors showed that in these circumstances, a large number of cells migrate into the intestinal lumen via M-cell-gated diapedesis.…”
Section: Role Of Intestinal Membranous Cellsmentioning
confidence: 99%